Biodegradation of Biocomposite Suture Anchor Implants 2, 2 years after Rotator Cuff Repair. Issue 7 (21st July 2017) - Sgroi, Mirco; Friesz, Theresa; Reichel, Heiko; Kappe, Thomas
Objectives: Arthroscopic rotator cuff repair is one of the most frequently performed operations in orthopaedic surgery. Resorbable PLLA or PGA implants have been reported to be associated with osteolysis. Biocomposite implants, composed of PLLA and/or PGA and ceramics, have gained popularity due to their biocompatibility and lack of osteolysis. The aim of the present study was to investigate the biodegradation progression of biocomposites suture anchor implants 2 years after rotator cuff repair. Methods: Twenty-five consecutive patients (84 implants) with arthroscopically repaired rotator cuff tears using screw-in biocomposite implants with a 5, 5 mm diameter and a minimum of 2 years (range, 16, 3 to 32, 0 months) follow-up were included into the present study. To analyse the biodegradation process of the suture anchors, an MRI of the operated shoulder was performed. The peri-implant fluid, the degradation of the suture anchors and the widening of the bone beds were assessed. Results: In the present study, the structure of the suture anchor implants was clearly visible in 23.8%, visible in 42.9%, partially visible in 23.8%, and not visible in 9.5%. No peri-implant fluid was observed in 26, 2%. Slight peri-implant fluid was seen in 34, 5%, a continuous fringe of fluid at least 1 mm thick in 23, 8% and more than 1mm thick in 13, 1%. The mean width of the bone beds was 4, 38 ± 1, 28 mm (apex), 5, 41± 1, 12 mm (middle) and 5, 88 ± 1, 39 mm (basis), indicating a widening of 0.33 mm of the basis. The mean length of the bone beds was 19, 09 ± 2, 38 mm. No significant difference was found between the lateral and medial row or between knotted and knotless implants. No case of gross osteolysis was observed. Conclusion: The results of the present study show that biocomposite suture anchors are frequently still visible on MRI 2 years after a rotator cuff reconstruction. No gross osteolysis was observed in the present study, indicating good biocompatibility of the implants.